Paul, military imagery and social disadvantage - J. Punt (Acta Theologica)
In the past, attention for the social position or standing of the early Jesus followers was overrun by concerns for the theological and religious dimensions of those communities. The role of the Roman Empire and the impact of its military forces on the lives of people have generated even less attention. Paul’s use of military images in the context of the Roman Empire underlines the prevalence and influence of the military, and provides an important perspective for understanding first-century social location.